117k views
5 votes
Given that a­­b = x, evaluate the following 2a^3b+a^2b+a^b

User Rambatino
by
6.4k points

2 Answers

3 votes

Answer:

2x^3+x^2+x

Step-by-step explanation:

since a^b = x, then you can just cross out that from each number and replace it with x

User Rudy Lattae
by
6.0k points
5 votes
Answer:

(3x^3)/(b^2) + x

Step-by-step explanation:
We will try to simplify the given expression into terms of ab and then substitute with ab = x as follows:
2a³b + a²b + ab
a² (2ab + ab) + ab
a² (3ab) + ab
a² (3x) + x

Since ab = x, therefore, a = x/b
Substitute with this in the above expression to get:
(x/b)²(3x) + x

(3x^3)/(b^2) + x

Hope this helps :)
User Erik Carstensen
by
5.8k points